Development of a Digital Directory Web for SMEs under the guidance of Telkom Witel South Surabaya - Yesa, Caesareano Lafado; Aulia, Darlin; Baskara, Dominggo Bayu; Maheswari, Irma Jauzalia; Fauziyah, Ihda; Darmawan Sutrisno, Rizki Putra (Abdi Masyarakat, 2023)
Results in MSME business turnover being hampered by limited capital and limited business diversification.Based on observations and interviews with Partners, there are main problems experienced by Telkom Witel South Surabaya-assisted MSMEs, namely how can they manage MSMEs and then introduce and sell their products with the widest possible reach so that they are not only in the Surabaya area and its surroundings so that Community Service activities are expected to provide contribution in terms of skills and abilities in generating profits and overcoming problems. The solution to solving this problem is to develop a digital directory as well as its features and functions within the organization at Telkom Witel, South Surabaya. The output that will be achieved in this activity is digital marketing efforts through the website which are expected to be able to increase profits and provide a sense of trust to consumers to be interested in buying the products offered. The results of this PKM activity include several calls for mandatory outputs, namely (1) scientific publications in national social service journals with ISSN, (2) activity videos, (3) increasing the application of science and technology in society (online platforms). The stages of PKM implementation consist of (1) developing a digital MSME web directory.